DEMANDING QUALITY SERVICE: AN EVALUATION OF THE WIRELESS APPLICATION SERVICE PROVIDERS ASSOCIATION (WASPA) CODE OF CONDUCT IN LIGHT OF THE CONSUMER PROTECTION ACT 68 OF 2008 - Leander Kruger; Monray Marsellus Botha (Obiter, 2017)
Consumerism has been around for quite some time, giving rise to the need to protect consumers against exploitation by suppliers. In the South African context the impetus to extend protection to consumers of goods and services however only gained proper momentum at the beginning of the 2000s. The Electronic Communications and Transactions Act 25 of 2002 was introduced to provide protection in respect of online transactions. With the introduction of the National Credit Act 34 of 2005 that affords protection to consumers in the credit market as well as the Consumer Protection Act 68 of 2008 that affords protection to consumers in a wide variety of instances consumer protection in South Africa has eventually reached an acceptable level. The CPA, being the most recent in the aforementioned trio of consumer protection legislation, is a comprehensive piece of legislation that extends protection to South African consumers in a wide variety of matters, inter alia, providing them with rights in respect of defective goods, contract terms, franchise agreements, auctions, product liability and so forth. The CPA was signed into law by the President on 24 April 2009 and was put into effect incrementally. The general effective date of the CPA is 31 March 2011 and the regulations issued in terms of the Act were published on 1 April 2011. The fast-developing mobile (cellphone) industry, where products and services improve constantly, necessitates the forging of consumer–brand relationships in order to keep consumers brand loyal and thus to prevent them from switching to competing brands. The South African cellphone industry has been characterised by major growth and is regarded as being one of the fastest-growing industries on the African continent. The number of cellphone users has more than doubled from 12 million in 2005 to 28 million in 2011, constituting 82% of the adult South African population. Competition between cellphone brands has also increased as a variety of different cellphone handsets and smart phones have started entering the South African market, making them accessible and affordable to South African consumers, as well as making it easier to switch between brands. South Africa has shown rapid growth in the number of cellphone users, leading the market to reach saturation. This rapid growth has also led to major network congestion and subsequent service problems related to the South African cellphone service provider networks. Subsequently, customers are showing high levels of customer dissatisfaction, requiring service recovery strategies to be put in place to remedy the situation. As it is impossible for service providers to consistently meet and exceed customer needs, service providers need to determine what remedies customers anticipate when their expectations are not met and service failures occur. If service providers are unable to recover from service failures, service providers could experience detrimental results to their profitability and performance, which could furthermore lead to customers switching service providers and engaging in negative word-of-mouth. According to Bejou and Palmer, it is important for a service business to determine their customer types and how long customers have been dealing with them (consumption stage), as this will influence how customers will react when faced with poor service and service failures and how easily they will switch to a substitutable product and new service provider. This note will examine the right to fair value, good quality, and safety in respect of services provided by mobile “service providers” in South Africa with particular reference to the CPA as well as the WASPA Code of Conduct for the mobile service provider industry.